2012
DOI: 10.3892/or.2012.1729
|View full text |Cite
|
Sign up to set email alerts
|

CD147 silencing via RNA interference reduces tumor cell invasion, metastasis and increases chemosensitivity in pancreatic cancer cells

Abstract: Abstract. CD147, which belongs to the immunoglobulin superfamily, is a multifunctional glycoprotein that has been shown to increase tumor invasion, metastasis and multidrug resistance. To define the role of CD147 in invasion and metastasis more precisely, we utilized gene silencing to inhibit the expression of CD147 in pancreatic cancer cells. We observed that CD147 expression was significantly impeded at both the mRNA and protein levels and resulted in a decrease of MMP-2 and MMP-9 activities. There was also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 33 publications
(43 reference statements)
0
14
0
Order By: Relevance
“…Further, MCT1 and MCT4 require expression of the plasma membrane glycoprotein CD147 for proper cell membrane insertion (17). Support for the importance of these processes has recently come from preclinical data demonstrating that inhibition or reduction of MCTs holds promise for cancer therapeutics (10, 18, 25, 39, 40). For example, MCT1 inhibition with α-cyano-4-hydroxycinnamate delays tumor growth, induces tumor core necrosis, and decreases tumor hypoxia in Lewis Lung carcinoma and WiDr human colorectal adenocarcinoma xenographs.…”
Section: Discussionmentioning
confidence: 99%
“…Further, MCT1 and MCT4 require expression of the plasma membrane glycoprotein CD147 for proper cell membrane insertion (17). Support for the importance of these processes has recently come from preclinical data demonstrating that inhibition or reduction of MCTs holds promise for cancer therapeutics (10, 18, 25, 39, 40). For example, MCT1 inhibition with α-cyano-4-hydroxycinnamate delays tumor growth, induces tumor core necrosis, and decreases tumor hypoxia in Lewis Lung carcinoma and WiDr human colorectal adenocarcinoma xenographs.…”
Section: Discussionmentioning
confidence: 99%
“…Degradation of the ECM at both the primary tumor site and at the secondary colonization site is critical for tumor invasion and metastasis [12]. Recently, the role of CD147 in tumor invasiveness was confirmed in several human malignancies, including gastric cancer [14][16]. Inhibition of CD147 expression by RNA interference reduced tumor cell invasion and tumorigenicity, as well as increased chemosensitivity to paclitaxel [17].…”
Section: Introductionmentioning
confidence: 99%
“…We also showed that HAb18G/CD147 was highly expressed in breast carcinomas and sarcomas (17), but its expression in pancreatic cancers were not included in that analysis. Although targeting CD147 by siRNA (27, 28) or monoclonal antibody (29, 30) can reduce cell growth and invasion in vitro and inhibits tumor growth and metastasis in a xenograft model, the role of HAb18G/CD147 in the early promotion of PDCA, especially in STAT3-involved PDCA initiation, remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%